Effects of the rove beetle, Dalotia coriaria, on western flower thrips, Frankliniella occidentalis, under laboratory conditions; and integrating the entomopathogenic fungus, Beauveria bassiana, with D. coriaria to suppress western flower thrips populations under greenhouse conditions - Li, Yinping (Kansas State University, 2019)
Western flower thrips, Frankliniella occidentalis, is one of the most destructive insect pests in greenhouse production systems due to direct and indirect plant damage resulting in substantial economic losses. In addition, western flower thrips has developed resistance to many insecticides. Therefore, alternative plant protection strategies are warranted, such as augmentative biological control. This research was designed to evaluate 1) the effect of different absolute numbers of predator (rove beetle, Dalotia coriaria) and prey (western flower thrips) on predation efficacy of rove beetle under laboratory conditions; 2) the effect of western flower thrips pupal stage, predator-prey ratio, predator-prey number, and searchable area on predation efficacy of rove beetle in the laboratory; and 3) the effectiveness and cost of integrating the entomopathogenic fungus, Beauveria bassiana, and the rove beetle, D. coriaria, in suppressing western flower thrips populations under greenhouse conditions. Three laboratory experiments were conducted to assess predation efficacy of rove beetle adults on three western flower thrips pupal stages [prepupa, pupa, and prepupa-pupa combination (50%:50%)]. In each experiment, there were six numbers (0, 1, 2, 3, 4, and 5) of rove beetle adults and four initial numbers (15, 20, 25, and 30) of one western flower thrips pupal stage. This treatment configuration allowed for assessing the effect of predator-prey ratios (1:5, 1:10, and 1:15), accounting for different initial prey numbers, on predation efficacy of the rove beetle. Overall, for each pupal stage, the estimated mean probability of western flower thrips adults captured on yellow sticky cards decreased as the number of rove beetle adults released increased from 1 to 3, although the effect of additional rove beetle adult releases was not apparent. Furthermore, across the pupal stages considered in this study, in general, there was no evidence of any differences due to predator-prey ratios or initial prey numbers within each predator-prey ratio. Two laboratory experiments were conducted to assess the effects of western flower thrips pupal stage, predator-prey ratio, predator-prey number, and searchable area on predation efficacy of rove beetle adults. In experiment 1, there were two western flower thrips pupal stages (prepupa and pupa), three predator-prey ratios (rove beetle:western flower thrips—1:5, 1:10, and 1:15), and three predator-prey numbers (2, 3, and 4 times). Experiment 2 evaluated the latter two factors in combination with searchable area defined by container sizes [15.2 cm (1,834.82 cm³) and 11.5 cm (701.79 cm³)]. The estimated mean probability of western flower thrips adults captured on yellow sticky cards was significantly higher for the 1:5 predator-prey ratio [61.1% (48.5-72.4%)] than 1:10 [39% (28.1-51.2%)] and 1:15 predator-prey ratio [34.7% (24.7-46.3%)]. The estimated mean probability of western flower thrips adults captured on yellow sticky cards for 2 times the predator-prey number [57% (44.3-68.8%)] was significantly higher than 3 [37.2% (26.6-49.3%)] and 4 [40.6% (30-52.3%)] times the predator-prey number. In addition, a significantly higher estimated mean probability of western flower thrips adults was captured on the yellow sticky cards in the 15.2 cm than 11.5 cm containers. Two greenhouse experiments were conducted that evaluated five treatments: combination of insecticides (spinosad, pyridalyl, chlorfenapyr, and abamectin), B. bassiana, D. coriaria, B. bassiana and D. coriaria combination, and a water control. Overall, the estimated mean number of western flower thrips adults captured on yellow sticky cards was significantly lower for the insecticide treatment (mean range: 0, 46) than for the B. bassiana and D. coriaria combination (mean range: 0.3, 105.1) over eight weeks. There were no significant differences in final foliage quality of chrysanthemum, Dendranthema x grandiflorum, plants among the five treatments in experiment 1, but there were significant differences in experiment 2. However, in experiment 2, the chrysanthemum plants across all treatments were not marketable due to substantial feeding damage by western flower thrips. The cost of the insecticide treatment was nearly twice that of the B. bassiana and D. coriaria combination ($963.50 vs. $495.67) and was over twice that of the B. bassiana only treatment ($963.50 vs. $417.04). The D. coriaria only treatment was the least expensive at $78.63. The results of the research provide insight into the predatory behavior of D. coriaria on western flower thrips pupal stages, which may have practical implications for greenhouse production systems. However, predation efficacy of rove beetle adults on western flower thrips is influenced by predator-prey ratio, predator-prey number, and searchable area. Finally, greenhouse producers must initiate insecticide applications or release rove beetle adults early in the production cycle when western flower thrips populations are low to minimize plant damage.
Keywords: Western flower thrips; Rove beetle; Predation efficacy; Laboratory; Greenhouse; Predator-prey ratio